Microscopic diagnostic study of inflorescences of Tagetes erecta plena L .var. "Hawaji" - Малюгіна, Олена Олександрівна; Malugina, E. A.; Смойловська, Галина Павлівна; Smoilovska, G. P. (БГМУ, 2017)
Резюме: были определены микроскопические диагностические признаки соцветий бархатцев прямостоячих высокорослой формы сорта «Гавайи». Основными микроскопическими диагностическими признаками Tagetes erecta plena L. var. «Hawaji» являются особенности строения эпидермы, характер устьичного аппарата, волосков, секреторных структур. Resume: the microscopic diagnostic signs of inflorescences of Tagetes erecta plena L. var.«Hawaji» were determined. The main microscopic diagnostic signs of Tagetes erecta plena L. var. «Hawaji» are features of the structure of the epidermis, stomata apparatus, trichomes, secretory elements.
Keywords: Tagetes erecta; flowers; microscopy investigation